Development and verification of a simulation model for paddy drying with different flatbed dryers - Van Hung, Nguyen; Martinez, Romualdo; Tuan, Tran Van; Gummert, Martin (Informa UK Limited, 2019)
This research developed a computer-based simulation model applicable for conventional and reversible airflow flatbed dryers, which can be used to predict the optimized time for mixing paddy (for the conventional flatbed dryer) and reversing the drying air (for the reversible air flatbed dryer). The developed software has the ability of simulating the paddy moisture content and temperature based on the input parameters of ambient (temperature and relative humidity) and drying air (temperature and airflow rate), dimensions of the dryers, and input grain properties and weight. The model was verified based on data collected from actual paddy drying practices in Vietnam from 1994 to 2015. Relative errors between modeled and measured moisture content of paddy varied for different stages of the drying process and different dryer capacities. On average, the error was highest at the middle stage of the drying processes. This error increased gradually during the early two-thirds stage of the drying process and reached 19% and 14% for the conventional and reversible air flatbed dryers, respectively. On the other hand, these errors decreased to less than 10% at the end of the drying process. Accurate prediction of optimized machine operating time determines the uniformity of the final moisture content of paddy between top and bottom layers, improving energy efficiency, and reducing postharvest losses and drying cost